THE INFLUENCE OF ARAB GEOGRAPHICAL RESEARCH ON PUPILS’ GEOGRAPHICAL CULTURE FORMATION - Amangeldi, O.; Kurt, T.; Tokayeva, L.; Nurbayeva, A. (Journal of Oriental Studies, 2025)
This article examines the influence of Arab geographical studies on the formation of pupils’ geographical culture. The analysis of school textbooks has shown that the achievements of Arab explorers and geographers are not sufficiently covered, leading to a one-sided perception of the history of geographical science. The study examined the achievements of Arab scientists, their contribution to world science, and possible ways of integrating this knowledge into the educational process. The research methodology included the analysis of scientific and historical sources, the study of school curricula, and a pedagogical experiment using new methodological approaches. In the course of approving the proposed methods in school practice, the level of pupils’ geographical culture and their ability to analyze the contribution of different civilizations was assessed. The results of the study showed that insufficient attention to the geographical achievements of the Arab world can be compensated by additional tasks and methodological recommendations for teachers. Introducing international issues into the school curriculum promotes global thinking, critical analysis, and intercultural communication skills. Thus, broadening the content of geography education through the study of Arab studies provides a more holistic view of the development of science. Keywords: Arab geographers, geographical science, geographical culture